Malcolm X [videorecording (DVD)] - Lee, Spike; Washington, Denzel, 1954-; Bassett, Angela; Hall, Albert; Freeman, Al. Jr., 1934-2012; Lindo, Delroy, 1952-; Haley, Alex (Distributed by Warner Home Video, 2010)
Born Malcolm Little, his minister father was killed by the Ku Klux Klan. He became a gangster, and while in jail discovered the Nation of Islam writings of Elijah Muhammad. After getting out of jail, he preaches the teachings, but later on goes on a pilgrimage to the city of Mecca. There he converts to the original Islamic religion and becomes a Sunni Muslim. He changes his name to El-Hajj Malik Al-Shabazz and stops his anti-white teachings, having discovered the error of his mistakes. He is later assassinated and dies a Muslim martyr.